The Role of School in Improving Dental and Oral Hygiene Education in Primary School Children Sukolilo 250 Surabaya - Sunomo Hadi; Imam Sarwo Edi; Endang Purwaningsih; Sri Hidayati; Ratih Larasati; Bambang Hadi Sugito; Ida Chairanna M; IGA Kusuma Astuti NP (Health Community Engagement, 2022)
Oral and dental health is an important thing, so the efforts to maintain oral health need to be developed from an early age. Health education targets or targets and health services that serve certain groups or populations are very supportive of a health program. One of the program series is an effort to order cadres of small dentists who are part of the School Dental Health Business (UKGS), their existence needs maximum attention. The methods implemented were cadre orders, oral health education, training and mentoring. The number of cadres is 20 students consisting of grades 3, 4 and 5. The extension methods used are lectures, questions and answers and associations. The aids used are dental models, posters, and props. The targets and outputs achieved in this service were the knowledge of cadres of small dentists about dental and oral health and minor dentists in maintaining dental and oral hygiene, skills songs of cadres of small dentists about oral health and minor dentists in carrying out maintenance. teeth and mouth, dental and oral health status and elementary school students so that they can support general health. After this activity is completed, cadres of small dentists can transfer knowledge to friends at school and the environment at home, so that the health status of their teeth and mouth will be better. dental and oral health status and elementary school students so that they can support general health. After this activity is completed, cadres of small dentists can transfer knowledge to friends at school and the environment at home, so that the health status of their teeth and mouth will be better. dental and oral health status and elementary school students so that they can support general health. After this activity is completed, cadres of small dentists can transfer knowledge to friends at school and the environment at home, so that the health status of their teeth and mouth will be better.The result of community service activities was an increase in the knowledge of school cadres in maintaining dental and oral hygiene for students at SDN Sukolilo 250 Kenjeran about maintaining dental and oral hygiene before and after the intervention of community service activities through group and individual counseling, as well as the clown performance that adapted to the model. education in children is pedagogic, learning while playing